Socio-Economic Conditions of Maid Servants - A Case Study of Ghaziabad City - Ahmed, Sarfraj (Journal of Commerce and Trade, 2015)
The socioeconomic transformation of Indian society in the present century and especially in the post-indipandence period in the form of industrialization, urbanization, westernization, spread of education and enhanced employment opportunities for women has brought about a series of perceptible changes in the status, outlook, worldview and attitude of Indian women, specially educated middle class women. Now, more and more woman have been coming out of the four walls of their homes in search of gainful employment which is evident from the slow but steadily rising Female Work Participation Rate (WRP) during the last three censuses. Maid servants as part of the unorganized labour are today victims of unmitigated hardships and indignities. They are paid shockingly low wages. There is no minimum wages fixed as the Minimum Wages Act does not cover the domestic workers. They do not have any job protection or security as they are hired and fired at the will and fancies of the employers. For even trivial reasons the maid servants can loose her their job if the employers desire so. In the absence of any suitable legal measures to protect the interests of domestic/maid servants their plight remains unchanged and they are victims of exploitation. The present paper aims to take up the task of exploring this new class of women workers, especially their working and living conditions.